FACTORS INFLUENCING THE USE OF DIGITAL TECHNOLOGIES IN THE ACTIVITIES OF SMALL BUSINESS ENTITIES AND SOLUTIONS TO ADDRESS THEM - To‘rayeva Nafisa (Modern American Journals, 2025)
This article is dedicated to analyzing the opportunities and challenges of using digital technologies in small business entities. The effectiveness of all digital data in small business is examined. The article highlights the socio-economic advantages of applying digital technologies for small businesses, the barriers encountered in the transition to a digital format, and the methods to overcome them. To study the factors influencing the development of small businesses under digital economy conditions, econometric models have been employed. The results of these analyses allow for forecasting the development trends of small business entities and defining directions for growth.
Keywords: Business Efficiency, Investments, Competitiveness, Analysis and Forecasting, Small Business, Digital Technologies, Digital Transformation.